2013
DOI: 10.1155/2013/524179
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Characterization of the Coordination Compounds of N-(2-hydroxymethylphenyl)-C-(3′-carboxy-2′-hydroxyphenyl)thiazolidin-4-one

Abstract: A dry benzene solution of the Schiff base N-(2-hydroxymethylphenyl)-3′-carboxy-2′-hydroxybenzylideneimine upon reacting with mercaptoacetic acid undergoes cyclization and forms N-(2-hydroxymethylphenyl)-C-(3′-carboxy-2′-hydroxyphenyl)thiazolidin-4-one, LH3 (I). A MeOH solution of I reacts with Co(II), Ni(II), Cd(II), Zr(OH)2(IV), and UO2(VI) ions and forms the monomeric coordination compounds, [M(LH)(MeOH)3] [where M = Co(II), Ni(II)], [M′(LH)(MeOH)] [here M′ = Cd(II), UO2(VI)] and [Zr(OH)2(LH)(MeOH)]. The coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The ](C-S)(thiophene) stretch [20] of the ligand shifts from 645 cm −1 to lower energy by 50 cm −1 in IV, while it remains unchanged in the rest of the compounds. The absence of a band in the region 835-955 cm −1 due to the ](Zr=O) stretch [21] 1135 cm −1 due to the (Zr-OH) bending mode [22] also support the proposed structure, V of the present Zr(OH) 2 (IV) compound. VI exhibits the ] (O=Mo=O) and ] as (O=Mo=O) stretches at 950 and 918 cm −1 , respectively, [22].…”
Section: Compoundsupporting
confidence: 77%
See 1 more Smart Citation
“…The ](C-S)(thiophene) stretch [20] of the ligand shifts from 645 cm −1 to lower energy by 50 cm −1 in IV, while it remains unchanged in the rest of the compounds. The absence of a band in the region 835-955 cm −1 due to the ](Zr=O) stretch [21] 1135 cm −1 due to the (Zr-OH) bending mode [22] also support the proposed structure, V of the present Zr(OH) 2 (IV) compound. VI exhibits the ] (O=Mo=O) and ] as (O=Mo=O) stretches at 950 and 918 cm −1 , respectively, [22].…”
Section: Compoundsupporting
confidence: 77%
“…Copper(II) acetate monohydrate, zinc(II) acetate dihydrate (SD's Fine); cobalt(II) acetate tetrahydrate, hexadecaaquaoctahydroxotetrazirconium(IV) chloride (BDH); ammonium molybdate(VI) tetrahydrate, acetyl acetone, methanol, triethylamine, chloroacetyl chloride (Ranbaxy); thiophene-2-carboxylic acid hydrazide (Acros Organics (USA)) were used as supplied for the syntheses. Bis(acetylacetonato)dioxomolybdenum(VI), hexadecaaquaoctahydroxotetrazirconium(IV) acetate, and 3-formylsalicylic acid were synthesized by following the mehods as reported earlier [8].…”
Section: Methodsmentioning
confidence: 99%
“…Much attention is being paid to coordination compounds as potential antimicrobial agents in recent times. This is due to the improved activity of drugs administered as complexes [1][2][3][4][5][6]. It has been suggested that ligands with nitrogen and oxygen donor systems might inhibit enzyme production.…”
Section: Introductionmentioning
confidence: 99%
“…II exhibits a strong band at 2855 cm −1 due to the intramolecular H-bonded OH groups of phenolic and/or carboxylic acid moieties [23]. The appearance of this band almost at the same energy in the coordination compounds of the Zr(OH) 2 (IV) and UO 2 (VI) ions is indicative of the noninvolvement of the The absence of a band in the region 835-955 cm −1 due to the ](Zr=O) stretch [29] [25]. The presence of a broadband at 3445 cm −1 due to coordinated OH group and the appearance of a new medium intense band at 1125 cm −1 due to the (Zr-OH) bending mode [25] also support the proposed structure of the present Zr(IV) compound.…”
Section: Infrared Spectral Studiesmentioning
confidence: 99%
“…exhibits the ] (O=U=O) stretch [31] at 920 cm −1 . The force constant ( U-O ) and U-O bond length in the present compound are 7.03 mdyn/Å and 1.73Å, respectively [25].…”
Section: Infrared Spectral Studiesmentioning
confidence: 99%